Handling victim blaming in cases of sexual violence against women (KBGO) by law number 12 of 2022 - Ishwara, Ade Sathya Sanathana (Journal of Law Science, 2025)
Women are considered vulnerable groups, accounting for the majority of sexual violence victims. People often place partial or complete blame on women for the sexual violence they have experienced. This relates to the concept of gender equality, patriarchal culture, and the mass media. This research aims to provide a comprehensive understanding of the Sexual Violence Crime Law through literature studies, based on the principle that the best interests of the victim can reduce and prevent the occurrence of victim blaming. The research method applied is normative legal research, which uses a statutory and conceptual approach. The results of this research demonstrate the existence of various forms of victim blaming, their associated impacts, and the role that the Law of the Republic of Indonesia Number 12 of 2022 concerning the Crime of Sexual Violence plays in preventing and reducing victim blaming. Therefore, we anticipate that the results of this study will enhance our understanding of criminal law, particularly in the context of handling victim blaming in sexual violence cases, and offer valuable insights for government and law enforcement officials in the areas of law enforcement, public order, and public peace.